Studies On The Properties Of Conductive Particulate Fillers Filled Rubber Composites [TS1892. A636 2008 f rb]. - Mat Junoh, Mohd Anuar (2008)
The use conductive fillers on properties of rubber composites were studied. Three types of conductive filler has been used in this study i.e. aluminium, zinc and carbon black.